Business Development Strategy Using Swot Analysis in an Effort to Improve Competitiveness at UD Sinar Terang - Sirri, Rohimah; Andarini, Sonja (Dinasti Publisher, 2026)
This study aims to formulate business development strategies to enhance competitiveness at UD Sinar Terang using SWOT analysis. The research employs a descriptive qualitative method, with data collected through interviews, observations, and documentation. The informants include the business owner, employees, suppliers, and customers. The results indicate that UD Sinar Terang's main strengths lie in friendly service, honesty, competitive pricing, product completeness, and strong relationships with customers and suppliers. However, weaknesses include manual recording systems, dependence on the owner, and potential operational errors. From an external perspective, opportunities include increasing construction activities, partnerships with contractors, and digital marketing potential. Meanwhile, threats mainly arise from intense price competition and the presence of numerous competitors. Based on IFAS and EFAS analysis, UD Sinar Terang is positioned in Quadrant I (Strength–Opportunity), indicating an aggressive strategy. Therefore, the recommended strategy is to leverage internal strengths to seize external opportunities, such as improving service quality, expanding market reach, and modernizing operational systems.